On the edge: Delays in election results and electoral violence in Sub-Sahara Africa - Ghadafi Saibu (German Institute of Development and Sustainability (IDOS), 2023)
Does the length of time passing between elections and the announcement of elections results increase the risk of post-election violence? The declaration of official election results is a crucial moment in the electoral cycle. When electoral management bodies (EMBs) take longer than expected to announce official election results, it can signal to the opposition that the election is being stolen. Following this logic, this paper argues that the length of time between elections and the announcement of the official results acts as a signal of possible voter fraud, thereby increasing incentives for post-election violence. Hence, the paper hypothesises that a long length of time between elections and the announcement of official results increases the risk of post-election violence. This hypothesis is examined with an original dataset of election results declarations in African countries from 1997 to 2022. After controlling for important confounders that could influence delays in reporting and violence, the article empirically demonstrates that a longer length of time between elections and the announcement of official election results increases the risk of post-election violence. In doing so, this paper makes a significant contribution to studies of elections, and electoral violence. Its provision of a new dataset on election results declarations in African countries is also a significant contribution.
Keywords: 320; Election violence; delayed elections; post-election violence; elections results declarations; announcement of elections results; Africa